Popular Confucianism and its Manifestations in Contemporary Chinese Societies - Chen, Yong (2016)
This article focuses on the conceptualization of popular Confucianism and addresses some of its manifestations—Ruzong Shenjiao, Yiguan Dao, and De Jiao, in this case—in contemporary Chinese societies. It will provide a relevant perspective to understand how Chinese have endeavored to employ popular Confucianism to construct meaning and identity in their respective societies.